An Investigative Study on the Effects of Pedagogical Agents on Intrinsic, Extraneous and Germane Cognitive Load: Experimental Findings With Dyscalculia and Non-Dyscalculia Learners - Ahuja, N.J. (Institute of Electrical and Electronics Engineers Inc., 2022)
Several studies have warranted the need to explore the relationship between pedagogical agents in the learning environment and the cognitive load on the learners, specifically, to study the influence on learner populations with different learning and motivation needs. The present work investigates the effects of the presence of a pedagogical agent in the learning environment on intrinsic, extraneous, and germane cognitive load for the dyscalculia and non- learner population. The proposed system intelligently investigates the learner, recommends an exclusive learning dyscalculia path and after tutoring assesses learning gain, and retention. Learner experience and effects of the pedagogical agent on types of cognitive loads are discussed on basis of post tutoring analysis. Samples of 82 learners have been studied, experimental findings based on research questions have been reported and conclusions discussed. Our assumption that 'a well-articulated and well-designed instructional design exerts a minimal extraneous cognitive load on learners and facilitates learning gain and retention' is consistent with the obtained results. The result concludes that pedagogical agent does not add to intrinsic and extraneous cognitive load. An improved Germane Cognitive load and a good amount of knowledge retention are noticed post learning. Â© 2013 IEEE.